Indirect Complaints by ESL learners in a Malaysian tertiary setting - Ting, Su Hie; Kai, Karen Ling Phang (2009)
While direct complaints to the source of the dissatisfaction aim to resolve problems, indirect complaints to a hearer not responsible for the matter of complaint may function to gain sympathy or to maintain social relationships with the speaker. This study examined the structure and language features of indirect complaints produced by ESL learners in a Malaysian tertiary setting. A total of 29 undergraduate students participated in a simulated indirect complaint task on a topic. The prompts comprised four topics related to a university student's life. The researcher acted as a silent but interested listener in the study. Results showed that the structure of the indirect complaints was introduction ^details ^evaluative statement ^problem solution ^ conclusion ^remark. The study found that the compulsory and optional stages were different from the structure of indirect complaints in low context communication contexts. Most of the participants did not provide a problem solution, and this gave opportunity for the listener to empathise with the problem and build rapport with the speaker. The implications of the findings on the teaching of cross-cultural communication skills in courses on communication in professional contexts are discussed.